2008
DOI: 10.1136/ard.2008.091801
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring anti-TNF  treatment in rheumatoid arthritis: responsiveness of magnetic resonance imaging and ultrasonography of the dominant wrist joint compared with conventional measures of disease activity and structural damage

Abstract: The most responsive measure of inflammation when evaluating anti-TNFalpha medication was a composite measure comprising MRI synovitis, tenosynovitis and bone marrow oedema, and this may be a promising outcome measure in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 46 publications
5
60
1
3
Order By: Relevance
“…RAMRIS is being used increasingly in trials of biological agents to measure changes in these markers for disease activities. Recent work has shown that in the cohort of patients receiving tumor necrosis factor alpha (TNFα) treatment, the MR total inflammation score displayed superior responsiveness to conventional measures of disease activity, indicating its promise as an outcome measure in clinical studies and for clinical practice [23].…”
Section: The Outcome Measures In Rheumatoid Arthritis Clinical Trialsmentioning
confidence: 99%
“…RAMRIS is being used increasingly in trials of biological agents to measure changes in these markers for disease activities. Recent work has shown that in the cohort of patients receiving tumor necrosis factor alpha (TNFα) treatment, the MR total inflammation score displayed superior responsiveness to conventional measures of disease activity, indicating its promise as an outcome measure in clinical studies and for clinical practice [23].…”
Section: The Outcome Measures In Rheumatoid Arthritis Clinical Trialsmentioning
confidence: 99%
“…Moreover, a wide variability was identified regarding the therapy assumed by the enrolled patients (etanercept, adalimumab, infliximab) and the follow-up, ranging from 12 weeks and 24 months. The number of joints evaluated was variable: some studies included a single joint (wrist) [75], other studies evaluated a great number of articular sites (78 joints assessed in the study conducted by Hammer et al in 2010) [77]. All studies demonstrated a significant reduction of US score after treatment with TNF-antagonist, irrespective of the follow-up.…”
Section: Main Applicationsmentioning
confidence: 99%
“…First, Hau and colleagues observed a significant reduction of the numbers of Doppler signals at MCP level in 5 RA patients [71]. From 2005, when OMERACT definitions were published, 12 studies evaluated the efficacy of anti-TNF drugs by using US assessment [11,16,17,21,24,25,[72][73][74][75][76][77]. The number of patients enrolled in the studies was variable, ranging from 18 to 278 patients.…”
Section: Main Applicationsmentioning
confidence: 99%
“…Erosions, bone edema, and synovitis depicted by MRI have been shown to cover all aspects of truth 12,13,14,15,16,17 , and the RA MRI score (RAMRIS) for erosions, bone edema, and synovitis has also demonstrated responsiveness and discrimination 18,19,20,21,22 . Although feasibility issues such as accessibility, time, cost, and patient compliance may cause limitations in clinical practice, MRI is acceptable for clinical trials.…”
Section: Imaging and Soluble Biomarkers In Ramentioning
confidence: 99%